Malang Mask Puppet Presentation Structure Arrangement of the Story Rabine Panji as Cultural Tourism Commodity in Malang Regency East Java - Suprihatin Dyah Pratamawati, Endang Wara (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
This research aimed to describe the model of structure arrangement of Malang Mask Puppet traditional art performance as the tourism commodity. The research method used was single case study with holistic single-case study approach toward the event program done by the traditional art performance group in Malang. It is done as an effort to maintain the existence of tradition art through tourism art performance arrangement. The result was the performance structure of the story (lakon) of Rabine Panji in Malang mask puppet performance. Malang mask puppet has been performed in shorter duration so that it became more interesting for the purpose of tourism.How to Cite: Pratamawati, E. W. S. D. (2016). Malang Mask Puppet Presentation Structure Arrangement of the Story Rabine Panji as Cultural Tourism Commodity in Malang Regency East Java. Harmonia: Journal of Arts Research And Education, 16(1), 66-74. doi:http://dx.doi.org/10.15294/harmonia.v16i1.4561